SUCCESSFUL CASE OF REMOVAL OF A WIRE THAT MIGRATED INTO THE PLEURAL SPACE AFTER CLAVICLE OSTEOSYNTHESIS. - Abidov Utkir Oktamovich (TADQIQOTLAR.UZ, 2024)
A unique case is described where a Kirschner wire, used for the osteosynthesis of a fracture at the proximal end of the left clavicle and stabilization of the sternoclavicular joint, migrated over five years from the surgical site. The wire moved through the posterior mediastinum, passing between the esophagus and the superior vena cava, and entered the right pleural cavity. The patient was successfully treated with a video-assisted thoracoscopic surgery.